2022
DOI: 10.1001/jamainternmed.2021.7382
|View full text |Cite
|
Sign up to set email alerts
|

Odds of Testing Positive for SARS-CoV-2 Following Receipt of 3 vs 2 Doses of the BNT162b2 mRNA Vaccine

Abstract: IMPORTANCE With the evidence of waning immunity of the mRNA vaccine BNT162b2 (Pfizer-BioNTech), a nationwide third-dose (booster) vaccination campaign was initiated in Israel during August 2021; other countries have begun to administer a booster shot as well.OBJECTIVE To evaluate the initial short-term additional benefit of a 3-dose vs a 2-dose regimen against infection of SARS-CoV-2.DESIGN, SETTING, AND PARTICIPANTS This preliminary retrospective case-control study used 2 complementary approaches: a test-nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 22 publications
9
153
3
1
Order By: Relevance
“…Israel was one of the first countries to immunize adults with the BNT162b2 vaccine and began offering a third dose of the same vaccine to older adults starting in July 2021. 23 Early data indicate that the third dose was associated with large reductions in the incidence of SARS-CoV-2 infection within 1 week after vaccination, with greater reductions in the second week. 23 The duration of protection offered by the third dose, however, is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Israel was one of the first countries to immunize adults with the BNT162b2 vaccine and began offering a third dose of the same vaccine to older adults starting in July 2021. 23 Early data indicate that the third dose was associated with large reductions in the incidence of SARS-CoV-2 infection within 1 week after vaccination, with greater reductions in the second week. 23 The duration of protection offered by the third dose, however, is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Early data indicate that the third dose was associated with large reductions in the incidence of SARS-CoV-2 infection within 1 week after vaccination, with greater reductions in the second week. 23 The duration of protection offered by the third dose, however, is uncertain. Many countries, including the United Kingdom and the United States, are now offering a third dose.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific rationale for boosters includes concerning evidence regarding declining vaccination protection over time and increased worries about breakthrough infections caused mainly by the SARS-CoV-2 Delta strain. The evidence for boosters comes from a variety of sources, including real-world data from Israel [ [11] , [12] , [13] ], the United Kingdom [ 14 ], and the USA [ 15 ], which showed that a booster dose of one of the commonly used mRNA-based vaccinations significantly reduces a person's chances of contracting SARS-CoV-2 and becoming mildly sick. A recent Pfizer research [ 16 ], which included data from over 44 000 people, indicated that after 6 months, vaccination protection dropped from 96.2% to 83.7%.…”
Section: “Omicron” Escalates the Covid-19 Vaccine Booster Debate: To Boost Or Notmentioning
confidence: 99%
“…Based on the positivity threshold and previously reported correlates of protection, those with prior infection could be protected from infection for >1 year after a single vaccination. While recent studies show that a third vaccination boosts antibody responses 29 and provides better protection against infection than two vaccinations 30 , and two vaccinations plus prior infection provides better protection against re-infection than prior infection alone 8 , a large part of the global population did not yet have the chance to get their first vaccination due to limited vaccine supplies. These results could inform vaccine strategies, providing an evidence-base to optimise population immunity in the context of resource limitations, while international SARS-CoV-2 immunisation programmes are scaled up and secured.…”
Section: Mainmentioning
confidence: 99%